Dirofilariose. Zoonose emergente negligenciada - da Silva, Rodrigo Costa [UNESP]; Langoni, Helio [UNESP] (My University, 2009)
Dirofilariasis is an unknown zoonosis, caused by Dirofilaria spp, nematodea most known as dog's heartworm (Dirofilaria immitis), which parasites the vascular system of these animals, but infects cats and human beings too. Its occurrence is highly linked to the presence of mosquitoes (Aedes spp., Anopheles spp., Culex spp.), adequate climatic conditions, as well as the transit between infection-free and endemic/ epidemic regions. Human beings can be infected by D. immitis (lung), Dirofilaria repens (lung, subcutaneous) and Dirofilaria tenuis (subcutaneous). The physiopathology is highly dependent of the parasite death, inducing the obstruction of the vascular system in dogs and nodular lesions with intense inflammatory reaction in pulmonary parenchyma, like a coin lesion, observed in the radiographs. It can be diagnosed by physical examination, microfilarias detection on the vascular system, enzymatic immunoadsortion (ELISA), radiographic alterations, echocardiography, ultrasonography and necropsy. There are risks on treatment and drug prevention in animals is the most efficient method, mainly in visits to endemic or epidemic areas, decreasing the risk to public health due to the parasite dissemination.
Dirofilariasis. Neglected emerging zoonosis
Keywords: Dirofilarias; Dogs; Man; Mosquitoes; Public health; Zoonosis